"Bold and bright, combining the aesthetics of comics and Saturday morning cartoons": an interview with comic book artist and writer Tom Scioli. Issue 5 (3rd September 2021) - Klaehn, Jeffery
ABSTRACT: Tom Scioli is a contemporary comics artist and writer who gained prominence as co-creator of Godland (Image Comics, 2005–13), an epic, Kirby-esque space opera which was nominated for an Eisner Award. His credits also include Transformers vs. GI Joe, 'Super Powers' (a run of short comics for DC's experimental imprint Young Animal) and, most recently, Go-Bots . He is known for his unconventional drawing style, dense page layouts, and imaginative writing. He's one of a small number of mainstream comics creators today who writes, draws, colors and hand-letters his work. This interview, undertaken throughout July-August 2018, explores his career in comics to date. Topics discussed include storytelling and graphic design, comic book formats, ways color impact comics and why coloring is so important in terms of art and its relationship with narrative and story, cinematic adaptations of comics (Thor, Fantastic Four), Jack Kirby's contributions and influence, Super Powers, He-Man and the Masters of the Universe, The Myth of 8-Opus, Transformers vs. GI Joe and Go-bots.